Liquid Hot Water Pretreatment of Miscanthus X giganteus for the Sustainable Production of Bioethanol - Nana Abayie Boakye-Boaten (BioResources, 2015)
The production of ethanol from lignocellulosic biomass provides an alternative to fossil fuels. In this study, liquid hot water (LHW)-pretreated Miscanthus x giganteus (MxG) was used to produce bioethanol through simultaneous saccharification and fermentation (SSF). MxG was pretreated at temperatures between 170 and 200 °C, for 5 to 15 min. The pretreatment was able to remove between 68.3% and 77.0% of the lignin present in the biomass. The highest percentage yields of sugars from pretreated MxG after enzymatic saccharification (32 °C, pH 4.5, 48 h), by a cocktail of two enzymes were 44.0% glucose and 42.0% xylose of theoretical. Ethanol concentrations between 0.780 and 3.715 g/L, and a high ethanol yield of 71.8% of theoretical were obtained using Saccharomyces cerevisiae (ATCC 24858) for fermentation. A comparison of scanning electron micrographs of the pretreated biomass showed morphological changes that enhanced the release of glucose and bioethanol yield.